(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the microbiological and radiographic features of patients with invasive pulmonary Aspergillosis treated at the National Lung Hospital. Methods: Retrospective descriptive study on 47 patients with invasive pulmonary Aspergillosis, treated at the National Lung Hospital from January 2019 to December 2020. Results: The average age was 54 ± 14 years old. Patients had host factors of EORTC/MSG were 63.8%, mainly hematological malignancies (34%) and long-term corticosteroid use (23.4%). Bronchoscopy features: Pseudomembrane (35.5%), necrotic nodule (21.9%), ulcer (20.6%), warty lesion, infiltration, purulent exudates were range from 10-14%. The most common lung lesions on chest CT are nodules (70.2%), consolidations (51.1%), and cavities (27.7%), multiple lesions appearing in both sides. Microbiological findings: sputum culture (50%), bronchoalveolar lavage culture (45.5%); blood galactomannan (66.7%), bronchoalveolar lavage galactomannan (40%); blood Aspergillus-specific lateral-flow device (LFD Aspergillus) (71.4%), bronchoalveolar lavage LFD Aspergillus (66.7%). Conclusion: Invasive pulmonary Aspergillosis has been reported increasingly. Early diagnosis and treatment reduce mortality. Combining the host factors, microbiological findings, and radiographic features helps clinicians establish diagnosis.